Respuesta :

We know  [tex]tan(A + B) = \frac{tanA + tanB}{1 - tanA * tanB}[/tex], and cotA = 1/tanA, so tanA = 5/6, since we inverse 6/5 to 5/6.

Now we substitute the values in the expression tan(A + B) = (tanA + tanB) / (1 - tan(A) * tan(B)) as follows:

(5/6 + 1/11) / (1 - 5/6 * 1/11) = (61/66) / ((66-5)/66) = (61/66) / (61/66) = 1

So, tan(A + B) = 1, now we have to make A + B the subject of the formula, so we find the arctan of 1.

tan(A + B) = 1

(A + B) = arctan(1) or tan^-1(1)

(A + B) = 45 degress, which is the value of arctan(1) or tan^-1(1)

Therefore A + B = 45degrees.

ACCESS MORE